(untitled) (Res Medica, 2014)
Recent events in the US, with the release of Anthrax Bacillus from as yet unknown sources, have for the first time in most people’s lifetime focussed the world’s attention on the threat of biological warfare. However, such attacks are not new. From time to time throughout history peoples and governments around the world have used microorganisms as efficient and cost-effective weapons of mass destruction. Starting in a rather crude but effective way, the Greeks and Romans deposited dead animals into their enemies’ drinking water. Later dead soldiers were added to this, and the technique was further refined in Medieval times when bodies of people who had died of infectious diseases were catapulted into towns under siege.